Finite elements in civil engineering applications : proceedings of the Third DIANA World Conference, Tokyo, Japan, 9-11 October 2002 /: proceedings of the Third DIANA World Conference, Tokyo, Japan, 9-11 October 2002. (2021) - Unknown
No abstract available